Analisis Pengaruh Pembelajaran Daring Terhadap Pemahaman Awal Mahasiswa Baru Pendidikan Fisika Pasca Pandemi - Japerson Robinsar Mulana Sembiring (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The research aims to analyze the influence of online learning on the initial understanding of new physics education students after the pandemic. The research method used is a quantitative research method using questionnaires which represent an important part of the survey process. The research was conducted at the Physics Education Study Program, FKIP, Riau University, with the research actors being new Physics Education students. The data collection technique used is a technique in the form of distributing questionnaires. The research results show that the majority of new physics education students experienced problems when learning online during high school, resulting in difficulties in understanding the learning material which affected the initial understanding they mastered after the pandemic.